Strategy for strengthening local culture-based character education in class iii students at SDN Menanga 1 - Santika, Ni Kadek Nila; Numertayasa, I Wayan; Darmayanti, Ni Wayan Sri (Sekolah Pascasarjana UPI, 2024)
Character education based on local culture is values education, character education, moral education, and character education which aims to develop students' abilities to make good and bad decisions, maintain what is good according to their outlook on life and science. This is a challenge for the author to study more deeply. This research was carried out to answer the following problems: The theoretical basis of this research is character education theory by Thomas Lickona, social learning theory by Bandura and behaviourism theory by Burrus Frederic Skinner. The type of research is qualitative research with a phenomenological approach. The technique for determining informants uses purposive sampling. Data collection techniques include observation, interviews, literature study, documentation and using qualitative data analysis, namely data reduction, data presentation and verification or drawing conclusions.